Arabic Language Teaching and Learning in Muslim Minority of West Papua - Ismail Suardi Wekke (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Islamic boarding school which well-known as pesantren establishment reflects a process of transformation on religious level of education. Arabic language is the compulsory subject to gain the set of curriculum. Therefore, it is a need to explore the process of Arabic language teaching and learning in the Islamic school. This research was conducted in Sorong greater area of West Papua. In-depth interview and non-participant observation were employed in collecting data. Arabic language is the main subject to support others subject. Each semester, students need to complete a set of subject. Some activities extend the subject in many courses to enrich language skill and capacity. In addition, Muslim minority is the environment to challenge the region. Therefore, the schools constructed the special program in complementing the syllabus. There is additional program to complete in one year program. The combination between classroom activity and course program is the breakthrough to extend opportunity to learn not only in the classroom but also outside classroom. This article concludes that additional program was created to enhance students' skill and language development through practices and non-formal courses.